Dynamic of biogenic amines and precursor amino acids during cabernet sauvignon vinification. (November 2018) - Henríquez-Aedo, Karem; Galarce-Bustos, Oscar; Aqueveque, Pedro; García, Apolinaria; Aranda, Mario
Abstract: The present study reports for the first time the dynamic of biogenic amines (BA) and precursor free amino acids (FAA) during Chilean Cabernet Sauvignon vinification applying a multi-matrix chromatographic method. BA (phenylethylamine, putrescine, cadaverine, histamine, tyramine, spermine, spermidine) and their precursor FAA (phenylalanine, ornithine, lysine, histidine, and tyrosine) were dansylated and quantified using liquid chromatography with fluorescence detection. Contrarily to previous studies, from the five wineries analyzed, only one showed the highest BA formation during malolactic fermentation (9.2 ± 0.1 mg L −1 ). The other wineries showed the highest formation during alcoholic fermentation ( n  = 1; 40.2 ± 0.3 mg L −1 ), in bottled wine ( n  = 2; 38.3 ± 0.0 and 168.6 ± 0.2 mg L −1 ), or without significant differences along vinification (<16 mg L −1 ). In all wineries a tendency between FAA decrease and BA increase was observed. Different BA and FAA profiles were observed with putrescine and lysine as the most prevalent amines. Toxicologically important amines, histamine and tyramine, were found in low concentrations (<3.5 mg L −1 ), except in one bottled wine that showed values of 8.4 mg L −1 and 8.1 mg L −1, respectively. It can be concluded that BA formation during Cabernet Sauvignon elaboration was moderately related with FAA content but without relation with FAA profile or a specific vinification stage. Highlights: A multi-matrix method was developed to determine biogenic amines and amino acids. Dynamic of biogenic amines and amino acids was studied in Chilean wines. Only one winery showed the highest biogenic amines level in malolactic fermentation. Biogenic amines were not determined by the initial level of precursors amino-acids.